Analysis of factors that cause financial distress in Islamic commercial banks - Lestari, Anisa; Rahmayanti, Dini (Journal of Accounting and Digital Finance, 2023)
This research aims to analyze the factors that cause financial distress in Islamic commercial banks in Indonesia so that Islamic banking companies avoid financial difficulties and reduce the possibility of bankruptcy. The population used in this research were 13 Islamic commercial banks registered with the Otoritas Jasa Keuangan (OJK), and sampling used a purposive sampling technique where samples were taken with certain conditions until 9 Islamic commercial banks were selected with a research period of eight years (2015-2022). Data analysis using multiple linear regression and the results obtained showed that the leverage ratio has a negative and significant effect on the occurrence of financial distress, where leverage measurement uses Debt to Equity Ratio (DER) and financial distress measurement uses Z-Score. At the same time, the liquidity ratio has a positive but insignificant effect on financial distress, where liquidity is measured using the Current Ratio (CR).